Effect of electroacupuncture on discomfort in patients undergoing colonoscopy: protocol for a multicentre, randomised, controlled clinical trial - Chao Lin; Wenting Chen; Yue Yong; Jiangang Song; Xiangyu Sun; Yongqiang Wang; Liyue Lu; Chunchun Wang; Kuangdi Xu (BMJ Open)
Introduction Colonoscopy is currently the most commonly used and effective method for early detection, diagnosis and treatment of tumours of the colon and rectum. However, similar to other invasive procedures, it is associated with adverse reactions such as pain and abdominal distension. Electroacupuncture (EA) has been proposed as a potential treatment for relieving this discomfort; however, there is limited evidence supporting its efficacy. Therefore, the aim of this study is to investigate the effectiveness of EA when used prior to colonoscopy.Methods and analysis This multicentre, randomised, controlled, patient–assessor-blinded trial will be conducted at three hospitals in China. A total of 500 participants will be randomly assigned to either the EA group or sham EA (SEA) group, in a 1:1 ratio. EA will be administered for 30 min before the colonoscopy. Participants will be asked to complete detailed questionnaires within 10 min after the procedure and 24 hours after the procedure to record their symptoms. The primary outcome will be assessed using discomfort numeric rating scale (NRS) scores. Secondary outcomes will include participants’ tolerance levels, including standard NRS scores for abdominal pain, bloating and anal discomfort reported by the participants, as well as heart rate(HR), blood pressure(BP), surgical pleth index, participant satisfaction, nurses’ and endoscopists’ evaluations, incidence of adverse events and salivary cortisol levels collected before EA and after colonoscopy.Ethics and dissemination Ethics approval was obtained from the Ethics Committee of Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine (number 2023-1327-94-01), Ethics Committee of Longhua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine (number 2023LCSY059) and Ethics Committee of Wuxi Hospital Affiliated to Nanjing University of Traditional Chinese Medicine (number 2023-062-01). The results of this study will be disseminated in peer-reviewed publications. All potential participants will be provided informed consent before participating in the study.Trial registration number ChiCTR2300073485.